2004
DOI: 10.1046/j.0022-202x.2004.22236.x
|View full text |Cite
|
Sign up to set email alerts
|

Terpinen-4-ol, The Main Component of Melaleuca Alternifolia (Tea Tree) Oil Inhibits the In Vitro Growth of Human Melanoma Cells

Abstract: The search for innovative therapeutic approaches based on the use of new substances is gaining more interest in clinical oncology. In this in vitro study the potential anti-tumoral activity of tea tree oil, distilled from Melaleuca alternifolia, was analyzed against human melanoma M14 WT cells and their drug-resistant counterparts, M14 adriamicin-resistant cells. Both sensitive and resistant cells were grown in the presence of tea tree oil at concentrations ranging from 0.005 to 0.03%. Both the complex oil (te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 52 publications
6
104
1
4
Order By: Relevance
“…Furthermore, bactericidal (Loughlin et al, 2008) and antifungal properties (Mondello et al, 2006) have also been found in terpinen-4-ol. Moreover, cytotoxicity of terpinen-4-ol on cancer cell lines, e.g., melanoma, has been reported (Calcabrini et al, 2004); which potently induces cell cycle arrest, apoptosis and necrotic cell death (Greay et al, 2010). There is no report of the clinically curative effect of terpinen-4-ol on cancer treatment, but terpinen-4-ol contained anti-inflammatory activity.…”
Section: Terpinen-4-ol Induces Autophagic and Apoptotic Cell Death Inmentioning
confidence: 98%
“…Furthermore, bactericidal (Loughlin et al, 2008) and antifungal properties (Mondello et al, 2006) have also been found in terpinen-4-ol. Moreover, cytotoxicity of terpinen-4-ol on cancer cell lines, e.g., melanoma, has been reported (Calcabrini et al, 2004); which potently induces cell cycle arrest, apoptosis and necrotic cell death (Greay et al, 2010). There is no report of the clinically curative effect of terpinen-4-ol on cancer treatment, but terpinen-4-ol contained anti-inflammatory activity.…”
Section: Terpinen-4-ol Induces Autophagic and Apoptotic Cell Death Inmentioning
confidence: 98%
“…Subsequent studies into the chemoprevention potential of perillyl alcohol were undertaken in National Cancer Institute-sponsored phase I, II, and III trials for prostate, breast, and colon cancers. Other lavender oil constituents, such as 1,8-cineole [52] and terpinen-4-ol [53], also display anticancer properties in vitro by inducing apoptosis in tumor cells. Nerolidol, a sesquiterpene found in some lavender essential oils, is also believed to have anticancer potential, as rats fed diets laced with nerolidol showed significantly reduced adenomas and the number of tumors per rat [54].…”
Section: Studies In Model Speciesmentioning
confidence: 99%
“…Furthermore, it can impair the growth of human M14 melanoma cells (Calcabrini et al, 2004) as well as induces necrotic cell death coupled with apoptotic cell death and arrests cell cycle at G1 stage in mouse malignant mesothelioma AE17 and murine melanoma B16-F10 cells (Greay et al, 2010). Further studies of potential anti-cancer drugs with a variety of cell lines are necessary, because there are high variability responses in different cancer cells following treatment with cytotoxic agents.…”
Section: Induction Of Intrinsic and Extrinsic Apoptosis Pathways In Tmentioning
confidence: 99%